Physicochemical characterization of micafungin and anidulafungin for its nebulized administration - Sonia Terradas-Campanario; Laura Gómez-Ganda; David Campany-Herrero (Farmacia Hospitalaria)
Objective: To determine by experimentation whether micafungin and anidulafungin possess physicochemical properties suitable for nebulization. Method: PH, osmolality, viscosity, density and chloride content were determined by pH monitoring, osmometry, viscometry, densitometry and potentiometry in two samples of different concentrations, 5 and 10 mg/mL each echinocandin. Results: The results obtained for micafungin solution were: pH 5.80 (0.14), osmolality 293.33 (1.53) mOsm/kg, chloride content 134.67 (0.58) mmol/L and density 1,009.4 (0,1) kg/m3; while for 10 mg/mL solution: osmolality 342.00 (1.00) mOsm/kg, chloride content 139.67 (0.58) mmol/L and density 1,014.5 (0.2) kg/m3. The results obtained for 5 mg/mL anidulafungin were: pH 4.22 (0.01), osmolality 464.67 (2.52) mOsm/kg, chloride content 137.00 (0.00) mmol/L and density 1,016.5 (0,2) kg/m3; while for 10 mg/mL solution: osmolality 656.33 (1.15) mOsm/kg, chloride content 132.00 (0.00) mmol/L and density 1,029.8 (0.4) kg/m3. Conclusions: PH, osmolality, chloride content and density values proved to be suitable for proper tolerability by nebulization.